A Proposal for Six Sigma Integration for Large-Scale Production of Penicillin G and Subsequent Conversion to 6-APA - Anirban Nandi; Sharadwata Pan; Ravichandra Potumarthi; Michael K. Danquah; Indira P. Sarethy (Journal of Analytical Methods in Chemistry)
Six Sigma methodology has been successfully applied to daily operations by several leading global private firms including GE and Motorola, to leverage their net profits. Comparatively, limited studies have been conducted to find out whether this highly successful methodology can be applied to research and development (R&D). In the current study, we have reviewed and proposed a process for a probable integration of Six Sigma methodology to large-scale production of Penicillin G and its subsequent conversion to 6-aminopenicillanic acid (6-APA). It is anticipated that the important aspects of quality control and quality assurance will highly benefit from the integration of Six Sigma methodology in mass production of Penicillin G and/or its conversion to 6-APA.